Cytokine gene expression, protein expression and genetic variability in the human response to infection - O'Dwyer, Michael J. (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2008)
In this thesis I explore the hypothesis that a pro-inflammatory cytokine immune response is a beneficial and protective host mechanism in the setting of the human response to infection. The various regulatory pathways involved in the control of this response are subsequently elucidated. Utilising the technique of quantitative real-time polymerase chain reaction, gene expression, at a messenger RNA level (mRNA), was assessed for a number of genes intimately involved in inflammation. Protein levels were also assayed using an enzyme linked immunosorbant assay technique and candidate genes were assessed for polymorphisms utilising either an amplifluor or taqman technique. Three patient groups were recruited which consisted of; 62 intensive care unit (ICU) patients with severe sepsis or septic shock (ICU group); 10 patients, from the general hospital wards, with a microbiologically confirmed gram negative bacteraemia and no organ failure or signs of an impending septic crisis (bacteraemia group); 13 healthy staff members (control group). Tumor necrosis factor alpha (TNFa) mRNA levels were elevated in the ICU group in comparison with the control group but were further elevated in the bacteraemia group. Similarly, interferon gamma (IFNy) mRNA was elevated in the bacteraemia group in comparison to the ICU group whilst interleukin 10 (IL-10) mRNA was greatest in the ICU group. In late sepsis there was an inverse relationship between both IFNy and TNFa gene expression and severity of illness and mortality.
Keywords: Clinical Medicine, Ph.D.; Ph.D. Trinity College Dublin